Especificação de um modelo para explicação e projeção de retornos do IBRX-100 - Mendes, Daniel Lorenzo (2015)
In this work, we propose an econometric model specification in the short form, estimating by ordinary least squares (OLS) and based in macroeconomic variables, with the goal of explaining trimestral returns of stock index IBRX-100, between 2001 and 2015. Besides, we tested the forecasting efficiency of the model and concluded that the forecast error estimated in a moving sample, estimating OLS at each round, and utilizing auxiliary VAR to forecast variables, is lower than forecast error associated to the Random Walk hypothesis in the one trimester forward horizon.